Relationship between Financial Factors and Access to Health Care and Quality of Life for HIV / AIDS Patients - Salma Ikmala, Laila; Nursalam, Nursalam; Ketut Alit Armini, Ni (Universitas Airlangga, 2021)
Introduction:Patients with HIV-AIDS experience various problems, one of which is related to financial factors and access to health services, this will also affect the patient's quality of life. The purpose of this study was to analyze the relationship between financial factors and access to health services.Method:This was a cross-sectional study with a sample size of 101 respondents who were selected using simple random sampling technique. The independent variable in this study is income and access to services, while the dependent variable in this study is quality of life. The instrument used was a demographic questionnaire and Health-Related Quality of Life, the data were analyzed using chi square with a significance level of p <0.05.Results:The results showed that there was a significant relationship between income (p = 0.044) and the availability of infrastructure (p = 0.003) with the quality of life of HIV-AIDS patients.Conclusion:The financial and access to healthcare factors are related to the quality of life of clients with HIV-AIDS, so that patients with good quality of life will show that the level of fulfillment of needs and access to health services is also good.